Verbeke Foundation : collages & assemblages - Canonne, Xavier, 1960-; Verbeke Foundation (Kemzeke, Belgium); Verbeke, Geert; Verboven, Marie ([Kemzeke, Belgium] : Verbeke Foundation, 2017)
An exceptional collection of roughly five thousand, particularly twentieth century, collages and assemblages lies at the heart of the private collection. A separate exhibition space has been specially designed to permanently display part of the collection. Not all of the works are on view, the exhibition is a subject to change four times a year.00The collection, which was developed around the art of mainly Belgian artists, encompasses collages from the early 1920s (Avant-Garde and Dada era) by Paul Joostens, Georges Herbiet, Henri Van Straten, Michel Seuphor, Marcel-Louis Baugniet and Jean-Jacques Gailliard. Collages created by surrealists such as E.L.T. Mesens, Marcel Mariën, Gilbert Senecaut, Louis Scutenaire, Jane Graverol, Rachel Baes, Robert Willems and Roger Van De Wouwer also form a part of the collection. 00A wide range of works by artists from the heydays of collage art (1950s through 1970s) has been included into the collection: Georges Collignon, Engelbert Van Anderlecht, Robert Geenens, Max Servais, Annie Debie, Louis Van Lint, Christian Dotremont, the Coll?Art movement (founded by Marcel-Louis Baugniet and Jean Milo). The collection also includes a series of works by authors, poets and art critics dating back to the same era: literary creations by Louis-Paul Boon, Hugo Claus, Freddy De Vree, Paul De Vree and Patrick Conrad.
Includes bibliographical references.
In Dutch, French and English.
Keywords: Verbeke Foundation (Kemzeke, Belgium) -- Catalogs; 1900-2099.; Art, Modern -- 20th century -- Catalogs; Art, Modern -- 21st century -- Catalogs; Art, Modern; Assemblage (Art) -- Catalogs; Assemblage (Art).; Collage -- Catalogs; Collage; Catalogs; Catalogs